PENGARUH LATIHAN DRIBBLE SLALOM TERHADAP KEMAMPUAN MENGGIRING BOLA PADA TIM SEPAK BOLA MAN 1 MUARA FAJAR PEKANBARU - Edwin Ade Saputra; Ramadi '; Kristi Agust (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The problem of the research is ability of Dribbling on Soccer team of MAN 1 Muara Fajar Pekanbaru hasn’t had a maximum skill, So when the player transfer the ball, they can’t across the enemies easily so they hardly to win the match . it can be seen from training and friendly match and this is one of the factor why they loss. This research was done at Soccer team of MAN 1 Muara Fajar Pekanbaru. This research used Experiment design to see the effect of using “Dribble Slalom”. The purpose of the research was to see the effect of using Dribble Slalom toward the ability of Drilling in Soccer team at MAN 1 Muara Fajar Pekanbaru. The population of this research was soccer team player of MAN 1 Muara Fajar Pekanbaru totaling 16 people. Exercise in this study is dribble slalom. The sampling technique used the total sampling, which was all the population had become the sample. The technique of collecting data was gotten from pre-test and post-test. The instrument of the research was a Dribbling test. The data analyzed by using T-test. Based on the data analysis, it can be seen from Tcount was 8,02 and Ttable 1,753. it meant Tcount>Ttable with the significant a=0,05. In conclusion, there was a different significant from Dribble Slalom in Soccer team of MAN 1 Muara Fajar Pekanbaru.Key Words: Dribble slalom, Dribbling Ability, soccer.